KONDISI PERAIRAN DAN PENDUGAAN IKAN DI TELUK CILETUH, SUKABUMI JAWA BARAT BERDASARKAN PROFIL NUTRIEN DAN MAKROZOOBENTOS : The Water Quality of Ciletuh Bay, Sukabumi, West Java Based on the Nutrient Profile and Macrozoobenthos - Yuniarti MS; Muhammad Wahyudin Lewaru; Wahyuniar Pamungkas; Ajeng Wulandari; Delilla Suhanda (Bogor Agricultural University, 2022)
Ciletuh Bay is a Global Geopark area since 2018 by UNCESCO. Ciletuh Bay is located in the south of Java Island which is directly facing the Indian Ocean, so Ciletuh Bays has unique water characteristics. This research aims to determine the condition of the waters of Ciletuh Bay in terms of physical, chemical, and biological parameters. This research was conducted in the dry season in June 2019 and the rainy season in February 2021. The parameters observed in this study were temperature, salinity, pH, dissolved oxygen, brightness, depth, ammpnia, nitrite, nitrate, phosphate, chlorophyll-a, sediment substrate, and macrozoobenthos. The results showed that the concentration of ammonia, nitrite, and chlorophyll-a had the highest values in the rainy season with values for each parameter of 0,028 mg/L; 1,663 mg/L; dan 2,82 mg/L. meanwhile, the highest concentration of nitrate and phosphate were found in the dry season with each having a value of 0,717 mg/L; dan 0,09 mg/L. The sediment substrate during both seasons is dominated by sand. Macrozoobenthos during the rainy season is dominated by the Gastropod class, while during the dry season it is dominated by the Bivalvia class.